2002
DOI: 10.1016/s0896-6273(02)00768-7
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Truncated MeCP2 Recapitulate Many Rett Syndrome Features and Display Hyperacetylation of Histone H3

Abstract: Mutations in the methyl-CpG binding protein 2 (MECP2) gene cause Rett syndrome (RTT), a neurodevelopmental disorder characterized by the loss of language and motor skills during early childhood. We generated mice with a truncating mutation similar to those found in RTT patients. These mice appeared normal and exhibited normal motor function for about 6 weeks, but then developed a progressive neurological disease that includes many features of RTT: tremors, motor impairments, hypoactivity, increased anxiety-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
607
5
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 713 publications
(664 citation statements)
references
References 40 publications
42
607
5
10
Order By: Relevance
“…Male pups carrying the X-linked null allele and heterozygous female pups were normal for many somatic and somatosensory measures, but had delays in a few behavioral reflexes, and also emitted higher numbers of ultrasonic calls on some postnatal days (see also 77 Moretti et al 79 conducted a systematic set of experiments to investigate social behavior in 10-week-old Mecp2 308/y mice. While no differences were observed in the resident-intruder challenge (see also 78 ), the mutant mice demonstrated significant social approach deficits in a partition test, in which a wild-type conspecific was located behind a clear, perforated barrier. Both the Mecp2 308/y mice and the controls preferred to investigate a novel conspecific versus a more familiar mouse; however, lower levels of social investigation were evident in the Rett syndrome model animals for both familiar and unfamiliar conspecifics.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 90%
“…Male pups carrying the X-linked null allele and heterozygous female pups were normal for many somatic and somatosensory measures, but had delays in a few behavioral reflexes, and also emitted higher numbers of ultrasonic calls on some postnatal days (see also 77 Moretti et al 79 conducted a systematic set of experiments to investigate social behavior in 10-week-old Mecp2 308/y mice. While no differences were observed in the resident-intruder challenge (see also 78 ), the mutant mice demonstrated significant social approach deficits in a partition test, in which a wild-type conspecific was located behind a clear, perforated barrier. Both the Mecp2 308/y mice and the controls preferred to investigate a novel conspecific versus a more familiar mouse; however, lower levels of social investigation were evident in the Rett syndrome model animals for both familiar and unfamiliar conspecifics.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 90%
“…30 -31 MeCP2 is originally considered to be a transcriptional repressor in conjunction with Sin3A and histone deacetylase, but was found later to also have a significant role as a transcriptional activator, as well as in the regulation of chromatin architecture and RNA splicing. [32][33][34] Thus, there is considerable complexity in the possible mechanisms by which MeCP2 can regulate gene expression.…”
Section: Dna Methylation Is a Key Mechanism For Repression Of Gene Exmentioning
confidence: 99%
“…The MeCP2 deficient mice and their wild-type littermates were purchased from the Jackson Laboratory (Bar Harbor, ME). 32 Fibroblasts were isolated from mouse and rat lungs by enzymatic digestion and then maintained in Dulbecco's modified Eagle's medium, supplemented with 10% plasma-derived serum (Cocalico Biologicals, Inc., Reamstown, PA), antibiotics; 1% insulin, transferrin, and selenium (Sigma Chemicals, St. Louis, MO); 5 ng/mL platelet-derived growth factor (R&D Systems, Minneapolis, MN); and 10 ng/mL EGF (R&D Systems) as before. 8 The adherent cells were then trypsinized and passaged for at least three times before use.…”
Section: Animals and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Mecp2 knockout mouse models demonstrated that MeCP2 is critical for the maturation and maintenance of neurons and glial cells [14,15]. Thereafter, Mecp2 knockout and knockin mice carrying mutations observed in RTT individuals allowed fundamental research to advance our understanding of the molecular, cellular, and systems-level pathology [16], and to begin addressing possible therapeutic interventions. These strategies have proved disease modifying, and have even resulted in full reversal of the underlying abnormalities [17].…”
Section: Introductionmentioning
confidence: 99%